Energy Prices and International Trade Incorporating Input-Output Linkages - Chan, H Ron (The World Bank, 2017)
.1 billion a year. Similarly, a carbon tax that unilaterally increases energy prices by 10 percent in the European Union could reduce European Union-wide net manufacturing exports by 1.9 percent annually